Lower bounds for the deviations of the best linear methods of approximation of continuous functions by trigonometric polynomials - Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
In the case of uniform approximation of continuous periodic functions of one variable by trigonometric polynomials, we obtain lower bounds for the Jackson constants of the best linear methods of approximation.